Pengembangan Media Pembelajaran Berbantuan Doratoon Berbasis Budaya Batak pada Mata Pelajaran Matematika Materi KPK dan FPB - Muhammad Tri Bintang; Dinda Yarshal (Lambda: Jurnal Ilmiah Pendidikan MIPA dan Aplikasinya, 2025)
This study aims to develop learning media assisted by Doratoon based on Batak culture in Mathematics subjects on KPK and FPB materials for grade V students of SD Negeri 067243 Medan Selayang, and to determine the feasibility of the developed media products. The research method used is development research (Research and Development) by using the ADDIE development model which consists of 5 stages, namely:Analysis, Design, Development, Implementation, And Evaluation. Data collection instruments in this study were observation, interviews and questionnaires. The data analysis technique used in this study was a questionnaire given to several expert reviewers, namely material expert reviewers, media expert reviewers and teacher and student responses. Based on the results of the study, it shows that the developed learning media is very feasible to be used in the learning process with the results of validation from material expert reviewers obtaining a percentage of 90.66%, media experts obtaining a percentage of 86.36%, student responses obtaining results of 98.28%, and teacher responses obtaining results of 95%. This media not only enriches mathematics learning with a local cultural contextual approach, but also increases student engagement and motivation to learn.